Kematangan Emosi Dan Pengambilan Keputusan Karir (Studi Kasus Siswa Kelas XII IPA 2 MA Al-Mardliyyah Waru Pamekasan) - Nawawi, Imam; Riadi, Ahsan; Mahmudah, Mahmudah (Jurnal Pengabdian Masyarakat dan Penelitian Thawalib, 2023)
In the adolescent stage a person will experience emotional development, namely high emotional development. Teenagers as one of the phases in human life are required to fulfill their duties in choosing a career and determining a career. This study aims to determine the emotional maturity of students and career decision-making abilities of class XII IPA 2 students at MA Al-Mardliyyah. The approach taken in this study is qualitative with a case study type of research. While collecting data using observation, interviews, and documentation. analysis used with data reduction techniques, data presentation, and conclusions. The results showed (1) the emotional maturity of class students was quite good. Students are able to vent negative and positive emotions at the right time and place. (2) students' career decision-making ability is quite good. Students are able to make career decisions according to their interests and talents, after graduating from school they will go on to college, and some will immediately choose to enter the world of work.